Teaching Writing At The Eighth Grade Of SMP Muhammadiyah 04 Sambi In 2015/ 2016 Academic Year - PRADIKA YULIANTI, DWI; , Drs. Djoko Srijono M.Hum; , Siti Fatimah S.Pd, M.Hum (2016)
This research aims at describing the implementation of teaching writing of Eight grade at SMP Muhammadiyah 04 Sambi. The objective of this study is to describe the teaching writing process at SMP Muhammadiyah 04 Sambi using inquiry-based learning. The writer applies descriptive research especially inquiry-based learning as a type of this research. The data are derived from event, informant, and document. The methods of collecting data nemely: observation, interview, and documentation. The technique of analyzing data are reduction, display, and verification. The result of this research shows in the following elements: 1) Learning objectives of teaching writing are divided into two. The general objective is to develop the writing skill of the learner competence which includes the knowledge about how to use English appropriately in writing about situation. 2) classroom procedure used by teacher is: first, opening, Building Knowledge of the Field (BKOF),Modeling of the Text (MOT), Joint Construction of Text (JCOT), Individual Constructing of Text (ICOT), and closing. Second, opening, Modeling of the Text (MOT), and closing. Third, opening, Joint Construction of the Text (JCOT), and closing. Fourth,opening, observation, dan reflecting. 3) Classroom techniques used by teacher are as follows: question and answer, discussion, role playing, games, giving feedback and summarizing. 4) The material used by the teacher was generally taken from some sources based on the syllabus. The teacher used textbook published by Kemdikbud as the printed material. 5) Theroles of teacher at SMP Muhammadiyah04 Sambi are as facilitator, group organizer, motivator and manager. 6) The roles of students at SMP Muhammadiyah o4 Sambi are as active participant, member of group, learner's monitor and evaluate their own progress. 7) The media used by the teacher at SMP Muhammadiyah 04 Sambi are: picture, texts. The teachers of SMP Muhammadiyah o4 Sambi do not always use all the component of Inquiry based teaching in teaching writing. Keyword: inquiry- based teaching, teaching writing